2004
DOI: 10.1021/cm034770w
|View full text |Cite
|
Sign up to set email alerts
|

Probing Molten Salt Flux Reactions Using Time-Resolved in Situ High-Temperature Powder X-ray Diffraction:  A New Synthesis Route to the Mixed-Valence NaTi2O4

Abstract: A new molten salt synthesis route to the mixed-valence sodium titanate NaTi 2 O 4 has been discovered. Reduction of Na 8 Ti 5 O 14 by Ti metal powder in a 3:1 molar mixture of NaCl:KCl at 770°C produced crystals of NaTi 2 O 4 . Use of the molten salt flux lowered the synthesis temperature of this compound by over 400°C. Time-resolved in situ high-temperature X-ray powder diffraction was used to probe the kinetics and mechanism of the reaction. Energydispersive X-ray diffraction (EDXRD) data revealed that the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 20 publications
2
41
0
Order By: Relevance
“…This is reminiscent of, e.g., the NaCl−KCl eutectics that were used to obtain NaTi 2 O 4 from Na 8 Ti 5 O 14 and Ti at moderate temperatures. 18 Further improvements in synthesis methodology are needed to obtain phase-pure samples, but these results demonstrate that CaFe 2 O 4 -type compounds can be obtained using the relatively benign conditions used here. The crystal structure of 1 and 2 contains double chains of edge-sharing MO 6 octahedra.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This is reminiscent of, e.g., the NaCl−KCl eutectics that were used to obtain NaTi 2 O 4 from Na 8 Ti 5 O 14 and Ti at moderate temperatures. 18 Further improvements in synthesis methodology are needed to obtain phase-pure samples, but these results demonstrate that CaFe 2 O 4 -type compounds can be obtained using the relatively benign conditions used here. The crystal structure of 1 and 2 contains double chains of edge-sharing MO 6 octahedra.…”
Section: Discussionmentioning
confidence: 85%
“…Difficult synthetic conditions (1200°C and a resistance furnace) are also used to get NaTi 2 O 4 from Na metal and TiO 2 , 16,17 although small crystals of NaTi 2 O 4 were obtained from Na 8 Ti 5 O 14 and Ti at 770°C using a KCl/ NaCl flux. 18 Overall, the relatively soft conditions used here to obtain 1 and 2 are of interest. It has recently been demonstrated that Na + in NaV 2 O 4 becomes mobile above 250 K, offering possible application in electrochemical energy devices.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, all of these methods require constant optimization as well as real‐time, in‐process monitoring. In the latter context, time‐resolved in situ high‐temperature X‐ray diffraction has been used recently to probe the kinetics and mechanism of a molten‐salt synthesis route towards the production of mixed‐valence sodium titanate, suggesting that the reaction occurred at the surfaces of the solid particles mediated by the molten‐salt flux 187…”
Section: Discussionmentioning
confidence: 99%
“…It has been used to synthesise low melting electroceramic powders 14 and high temperature complex oxide powders (e.g., MgAl 2 O 4 ). 15 The purpose of this work is to use MSS for the preparation of ZnAl 2 O 4 powder by heating equimolar ZnO and Al 2 O 3 powders in alkaline chlorides (LiCl, NaCl or KCl).…”
Section: Introductionmentioning
confidence: 99%